Collaborative open training with serious games: Relations, culture, knowledge, innovation, and desire - Oihab Allal-Chérif; Marc Bidan (Journal of Innovation & Knowledge (JIK), 2017)
This article studies the convergence between MOOCs (massive open online courses) and serious games, two new types of information systems designed to improve learning. The aim of this research is to identify the areas of influence in collaborative open training serious games developed by large firms for a significant cost and made available for free to the public and to students according to the same principles as MOOCs. The methodology of this exploratory research is based on Kurt Lewin's (1945) statement "nothing is so practical as a good theory" and takes the opposite view. The deep observation of three serious games from L'Oréal, IBM, and Thales results in a theoretical model with five distinct influence domains of serious games: relations, culture, knowledge, innovation, and desire. This model is then discussed and tested on eight other serious games from major industrial companies such as General Electric, Nestlé, and Cisco.
Keywords: M53; 650; Serious game; MOOC; Open training; Collaboration; Knowledge; Innovation